KETERAMPILAN CUCI TANGAN ANAK USIA 3 hingga tahun 5 TAHUN MELALUI TAYANGAN VIDEO CUCI TANGAN DI KB CAHAYA ILMU KABUPATEN BLITAR - Prayogi, Wahyu Fatma Setia; Yulindahwati, Asworoningrum; Wandi, Wandi (Jurnal Pendidikan Kesehatan (e-Journal), 2023)
Handwashing teaching is important to make lifeskills habituation, especially for preschollers, because they’re easy to imitate. This research’s aim to determine the increase in handwashing skills of toddlers aged 3 until 5 years with video. The design used single group pretest and posttest on 26 of 36 total student in KB Cahaya Ilmu, Blitar Regency. Data was collected by checklist and analyzed by Wilcoxon Signes Rank Test. The results showed that watching video had an effect on preschollers ability in handwashing. In conclusion, handwashing video can help developes preschollers’s handwashing skills